ISLAMIC EDUCATION VALUES IN BUILDING A SPIRIT OF RELIGIOUS HARMONY IN WINDU VILLAGE - Ainul Khalim (Universitas Islam Malang, 2021)
Windu Village is one of the villages in the Karangbinangun District, Lamongan which has itsuniqueness, ownnamely the existence of two adherents of different religions, namely Islam and Christianity who live in harmony with one another. The creation of this harmony cannot be separated from the values ​​of Islamic education taught in the village of Windu, whether organized by schools or the community. The purpose of this study is to describe, analyze, and interpret the phenomena of socio-cultural life based on empirical data obtained in the field (ideographical) regarding: 1) the values ​​of Islamic education which are used as a foothold in building religious harmony in Windu Village, Karangbinangun District. Lamongan; 2) reasons for the practice of Islamic education as a spirit to build religious harmony in Windu Village, Karangbinangun Lamongan District; and 3) the process of implementing Islamic education to build religious harmony in Windu Village, Karangbinangun Lamongan District. This research is a qualitative research with a type of phenomenology. Data collection techniques using participant observation techniques, in-depth interviews, and documentaries. The technique of determining informants using purposive sampling and snowball sampling techniques. The data analysis technique uses the interactive model analysis technique of Miles and Huberman. While the data validity test technique used triangulation technique. The results of this study indicate that: first, the values ​​of Islamic education which are used as a foundation in building religious harmony in Windu Village are the values ​​of knowing each other (ta'aruf), moderate (tawasuth), tolerant (tasamuh), mutual help (ta'aruf), moderate (tawasuth), tolerant (tasamuh), mutual help (ta'aruf). 'awun), and balance or harmony (tawazun).